Civil Religion dalam Rajutan Keagamaan NU - Wahyudi, Chafid (ISLAMICA: Jurnal Studi Keislaman, 2011)
The basic question that this paper tries to answer is, is it possible for the values of different âoften contending- religions in a single country to be the basis for the nationhood? Or, can the values of a single religion in a country where different religions exist be the basis of the state? The answer that this paper propagates is certainly no. But another question arises. What then the values âassuming that values are a must in a society or country as a term of moral reference- that must be adopted by all? It is toward answering this question that this paper is aimed at. It argues that religious values are universal and meaningful for human kind. They can serve as the basis for human benefit and well-being. But these values âoften originated from different religions- must not only be accommodated but also be reconciled. And the reconciling concept cannot be a religion, for that would mean that we support one religion at the expense of others. Hence this paper proposes that what has commonly been known a civil religion be the common ground -the sacred canopy as it were- in which various religious values can be integrated. It is in other words, the integrating mechanism for different religious values, which in turn can bring the social and political harmony for all citizens. The paper will discuss particularly this notion by referring to the concept of the Nahdhatul Ulama (NU) on nationhood and national identity.